Foundations of Financial Management - Block, Stanley B.; Hirt, Geoffrey A. (Homewood, Ill. : Irwin, 1987)
With the same contemporary approach and dynamic examples that made previous editions so popular, this edition continues to provide students with a focused understanding of today's corporate finance and financial management.
Includes bibliographies and index.
opc 10/1/17
Loans
Keywords: Corporations, Finance; Business Enterprises--Finance